Implication of The Constitutional Court’s Decision No. 91/Puu-XVIII/2020 on The Formal Examination of Law No. 11 of 2020 - Sri Warjiyati; Zeti Nofita Sari; Nur Lailatul Musyafaah; Dina Imam Supaat (Jurnal Jurisprudence, 2024)
ABSTRACT Purpose of the study: This paper aims to analyze the impact and implications of Constitutional Court Decision No. 91/PUU-XVIII/2020 on the formal review process of Law No. 11 of 2020. This includes an understanding of changes in the legal framework relating to the formal review process of the law and how the decision affects the formal review of the law. Methodology: This paper employed the normative legal research method through a jurisprudence approach and a statute approach. This research examined primary and secondary legal materials. Results: The Constitutional Court Decision No. 91/PUU-XVIII/2020 reflects the commitment of that highest justice institution to maintaining the enforcement of constitutional principles in the law-making process in Indonesia. It decided that the Law on Job Creation had a conditional unconstitutional status, as it did not follow the procedures of law formation stated in Law No. 12 of 2011. Even though it has a conditional unconstitutional status, the Law on Job Creation still applies until it is improved in two years by the government and the Legislative House. Applications of this study: This research is useful for providing valuable insight for policymakers, lawyers, and constitutional law practitioners regarding the practical implications of Constitutional Court decisions on the process of proposing laws. It can also help people understand how this ruling affects laws and policies in Indonesia. Novelty/Originality of this study: The novelty of this research lies in its special focus on Constitutional Court Decision No. 91/PUU-XVIII/2020 and its impact on the formal review of Law No. 11 of 2020. Apart from that, this research provides an important contribution to the concreteness of the Constitutional Court's formal legislative procedures. Keywords: Implications, Constitutional Court Decisions, Formal Tests.   ABSTRAK Purpose of thestudy (Tujuan): Penelitian ini bertujuan untuk menganalisis dampak dan implikasi dari Putusan Mahkamah Konstistitusi No. 91/PUU-XVIII/2020 terhadap proses uji formil Undang-Undang No. 11 Tahun 2020. Ini mencakup pemahaman tentang perubahan-perubahan dalam kerangka hukum yang berkaitan dengan proses uji formil undang-undang dan bagaimana putusan tersebut mempengaruhi pengujian formal undnag-undang. Methodology (Metodologi): Penelitian ini menggunakan metode penelitian hukum normatif melalui pendekatan jurisprudensi dan pendekatan perundang-undangan. Penelitian ini mengkaji bahan-bahan hukum primer dan sekunder. Results (Temuan): Putusan Mahkamah Konstitusi Nomor 91/PUU-XVIII/2020 merupakan cerminan komitmen lembaga peradilan tertinggi tersebut dalam menjaga tegaknya asas-asas konstitusi dalam proses pembentukan undang-undang di Indonesia. Putusan ini menyatakan bahwa UU Cipta Kerja berstatus inkonstitusional bersyarat, karena tidak mengikuti tata cara pembentukan undang-undang sebagaimana yang tercantum dalam UU Nomor 12 Tahun 2011. Meskipun berstatus inkonstitusional bersyarat, UU Cipta Kerja tetap berlaku sampai ada perbaikan dalam jangka waktu dua tahun oleh pemerintah dan DPR. Applications of this study (Kegunaan): Penelitian ini berguna untuk memberikan wawasan yang berharga bagi para pembuat kebijakan, pengacara, dan praktisi hukum konstitusi mengenai implikasi praktis dari putusan Mahkamah Konstitusi terhadap proses pengajuan undang-undang. Penelitian ini juga dapat membantu memahami bagaimana putusan tersebut memengaruhi hukum dan kebijakan di Indonesia. Novelty/Orginalty of this study (Kebaruan/Orisinalitas): Penelitian ini menawarkan kebaruan karena ia memberikan okus khusus pada Putusan Mahkamah Konstitusi No. 91/PUU-XVIII/2020 dan dampaknya terhadap uji formil undang-undang No. 11 Tahun 2020. Selain itu, penelitian ini dapat memberikan kontribusi penting terhadap kekonkretan putusan Mahkamah Konstitusi terhadap prosedur legislatif formal. Kata Kunci: Implikasi, Putusan MK, Uji Formil.